Pengaruh CR, ROE, dan FAR terhadap Struktur Modal yang Dimoderasi oleh Ukuran Perusahaan pada Sektor Pertambangan - Lusya Putri; Esi Fitriani Komara (Yayasan Literasi Sains Indonesia, 2025)
The objective of this investigation is to evaluate the influence of CR, ROE, and FAR on the capital structure within the mining sector, moderated by company size, spanning from 2019 through 2023. The study encompasses a population of 71 mining firms listed on the Indonesia Stock Exchange. This research was conducted because of the gap between the mining export value data and the capital structure value, where the export value data shows a graph that tends to increase but is followed by an increasing capital structure value. Not only that, this research is important because the mining sector has a high level of funding risk, so understanding the factors that influence capital structure is crucial for financial decision making. A purposive sampling approach was used to select the sample, based on the criteria set by the researcher, a sample of 53 companies was obtained. This research employs panel data sourced secondarily. It adopts a quantitative methodology. Data were acquired through documentation and processed via editing and tabulation. Analytical methods employed encompass descriptive statistics, classical assumption testing (including multicollinearity and heteroscedasticity tests), panel data regression, and moderated regression analysis (MRA). This study revealed that CR and ROE exert a partially adverse impact on capital structure, while FAR shows no significant effect. The capital structure is jointly influenced by CR, ROE, and FAR. Company size serves to mitigate the influence of ROE on capital structure.